Performance and emissions analysis of a diesel engine directly fuelled with waste cooking oil biodiesel. Issue 4 (19th May 2017) - Yang, Hao; Li, Xinghu; Mu, Mingfei; Kou, Guiyue; Li, Lijun
ABSTRACT: This research focuses on a comparative study of the physical and chemical properties of waste cooking oil (WCO) biodiesel with China stage IV diesel fuel. The estimate method of excess air ratio and the heating value ratio of an engine's cylinder mixture are proposed based on the differences of properties of two fuels. The bench tests of engine performance are carried out with an engine fuelled with two fuels separately. The estimated excess air ratio and the heating value ratio of an engine's cylinder mixture through the method are approximate to the experiment results. This comparison demonstrates that the estimate method can be applied to the performance analysis of an engine. Compared with China stage IV diesel, when a diesel engine is fuelled with WCO biodiesel, the torque and power decline from 1.9% to 13.8%; the brake-speciﬁc fuel consumption rises from 3.7% to 15.6%; CO, HC and PM emissions decrease significantly and NO X emissions increase slightly.